Stiffness evaluation of continuum robots based on the energy method and castigliano’s second theorem - Yang, Mengxue; An, Zhicheng; Lin, Zechen; Wang, Yuhang; Pang, Tongtao; Du, Fuxin (Frontiers in Robotics and AI, 2025)
IntroductionContinuum robots are studied and applied in neurosurgery due to their high flexibility and adaptability. The basic performance of continuum is mainly evaluated by stiffness, but there is no systematic and universal evaluation system.MethodsIn this paper, a general experimental platform for continuum robots is designed, based on which the fundamental performance of the notched continuum robot used in neurosurgery is evaluated. The continuum stiffness evaluation method based on energy method and Castigliano’s second theorem is proposed. By solving the internal force and energy of the notched continuum in sections, the stiffness model of single-segment and double-segment series continuum is established. The relationship between the stiffness of the continuum and the bending angle is obtained.ResultsThe simulation and experimental results show that under the condition of small deformation angle, the spatial stiffness model obtained by strain energy basically conforms to the actual model, which verifies the correctness and rationality of the stiffness calculation method proposed in this paper.DiscussionThis paper is of significant importance to promote the performance evaluation and optimization of continuum.